Pengaruh rasio profitabilitas dan good corporate governance terhadap kinerja keuangan perusahaan perbankan - Juliansyah, Muhammad Hafiz; Tripermata, Lukita; Munandar, Aris (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study is to analyze the financial performance of banking companies traded on the Indonesia Stock Exchange between 2018 and 2021 in relation to profitability ratios and corporate governance. Quantitative methods were used for this study. Purposive sampling was used to select 15 banking companies included in this study that are traded on the Indonesia Stock Exchange. Descriptive statistics were used to analyze the data in this study. Common effect, fixed effect, chow test, Hausman test, lagrange multiplier test, F test, t test, and coefficient of determination (R2) test were used during the model selection process. The F test shows that there is a positive and statistically significant correlation between the variables ROA and Institutional Ownership with CAR in banking companies listed on the Indonesia Stock Exchange from 2018 to 2021.